Self-Concept and Self-Esteem: Relevant Variables in the Life Satisfaction of Teachers - Óscar Gavín-Chocano; Guillermo Sanz-Junoy; David Molero (Education Sciences)
Over the last two decades, the number of people who practice activities in the natural environment has increased and the demand for teachers for these activities has grown. It is necessary to analyze the impact of different psychosocial and emotional factors, such as self-concept, self-esteem, satisfaction with life and well-being, in teachers of special regime sports education, as regulated training in the Spanish educational system. The purpose of this study is to analyze the relationship between physical, emotional and social self-concept and self-esteem and to study the influence of self-esteem between self-concept and life satisfaction in teachers. The participants of the study were 788 teachers of special regime sports education, from the regulated training educational system of Spain. The instruments used were the Self-Concept-Scale-AF5, the Rosenberg Self-Esteem Questionnaire and the Satisfaction with Life Scale. To present the results of the study, a structural equation model, PLS-SEM, was developed based on the theoretical framework analyzed, with an explanatory-predictive approach. The evidence showed the coefficients of determination for self-esteem (R2 = 0.395; Q2 = 0.268) and life satisfaction (R2 = 0.334; Q2 = 0.237) as being the appropriate adjustment. The acquisition of an adequate self-concept and correct self-esteem allows practitioners of sports disciplines in the natural environment to have greater life satisfaction.